PROGRAM EDUKASI “HOW TO BE AN IMPACTFUL YOUNGPRENEUR” PADA SISWA SMA TRI KARYA SURABAYA - Sitepu, Sri Nathasya Br; Michelle, Michelle (Universitas Sanata Dharma, 2023)
The IBM Goes to School community service program is held with the aim of equipping Tri Karya High School students with skill sets that can support the creation of youngpreneurs in Indonesia. The problems faced by students are related to the tendency to have a fixed mindset and lack of courage to get out of their comfort zone. Educational program with the theme